Compositional marker in vivo reveals intramyocellular lipid turnover during fasting-induced lipolysis - Thankamony, Ajay (Sci Rep, 2018)
Intramyocellular lipid (IMCL) is of particular metabolic interest, but despite many proton magnetic resonance spectroscopy ((1)H MRS) studies reporting IMCL content measured by the methylene (CH(2)) resonance signal, little is known about its composition. Here we validated IMCL CH(3):CH(2) ratio as a compositional marker using (1)H MRS at short echo time, and investigated IMCL content and composition during a 28-hour fast in 24 healthy males. Increases in IMCL CH(2) relative to the creatine and phosphocreatine resonance (Cr) at 3.0 ppm (an internal standard) correlated with circulating free fatty acid (FA) concentrations, supporting the concept of increased FA influx into IMCL. Significant decreases in IMCL CH(3):CH(2) ratio indicated a less unsaturated IMCL pool after fasting, and this compositional change related inversely to IMCL baseline composition, suggesting a selective efflux of unsaturated shorter-chain FA from the IMCL pool. This novel in vivo evidence reveals IMCL turnover during extended fasting, consistent with the concept of a flexible, responsive myocellular lipid store. There were also differences between soleus and tibialis anterior in basal IMCL composition and in response to fasting. We discuss the potential of this marker for providing insights into normal physiology and mechanisms of disease.